Investigating the effect of augmented reality-based virtual patient training on occupational therapy students’ clinical decision-making: A quasi-experimental study - Farshid Chahartangi; Nahid Zarifsanaiey; Manoosh Mehrabi; Bahareh Zeynalzadeh Ghoochani; Nahid Sharifzadeh (PLoS ONE, 2026)
Technology-enhanced education is an essential element of modern universities, improving clinical decision-making, and student performance. This study aimed to design and evaluate an augmented reality-based virtual patient (VPAR) educational model to enhance clinical decision-making in upper limb nerves among occupational therapy students. This quasi-experimental study conducted from January to April 2025 with 44 occupational therapy students from Shiraz and Arak Universities of Medical Sciences. Classes were assigned by pre-existing cluster allocation to the intervention group (VPAR, n = 24) or the control group (traditional education, n = 20). Clinical decision-making skills were assessed before and one month after a three-week VPAR program using a researcher-developed questionnaire. Data were analyzed using R software (version 4.3.3) and the Generalized Estimating Equations (GEE) model to determine the effect of the intervention. The post-test probability of a correct response was 7.34 times greater than the pre-test (p = 0.0684), indicating improved performance likely due to the intervention (p = 0.0018). Additionally, the intervention group had a 3.75 times higher likelihood of correct responses compared to the control group (p = 0.0004), demonstrating the intervention’s positive impact. In conclusion, the VPAR is an effective tool for enhancing clinical decision-making among occupational therapy students.